PALM OIL FUEL ASH (POFA) BINDER IN A NOVEL ENCAPSULATION OF 16 POLYCYCLIC AROMATIC HYDROCARBONS IN PETROLEUM SLUGDE : LEACHING BEHAVIOUR - ROSLEE, NOOR FAIZA (2024)
Solidification/Stabilization (S/S) method with cement as binder to remediate metals contained in petroleum sludge has been successfully proven previously. However, this technique was less successful to remediate organic contaminants since high concentration of Polycyclic Aromatic Hydrocarbons (PAHs) were detected in the sludge. This study focuses on remediating 16 PAHs compounds in petroleum sludge with Palm Oil Fuel Ash (POFA) used as cement replacement by using the S/S method. The S/S matrices were tested for PAHs leaching behaviour and strength after 7 and 28 days by air curing. The leaching test was measured by using the Toxicity Characteristics Leaching Procedure (TCLP) and the remaining PAHs concentration in the matrices was analyses by using Gas Chromatography Mass Spectrometer (GC-MS). The 16 PAHs were measured in Ordinary Portland Cement (OPC), POFA and Petroleum Sludge (PS) and the results show that all PAHs concentration in cement and POFA were below the standard limit. However, four PAHs compounds in the petroleum sludge, namely, Benzo (a) anthracene, Benzo (a) pyrene, Dibenzo (ah) anthracene and Indeno (1,2,3-cd) pyrene were above the standard limit and required further treatment. Based on the performance of S/S matrices in compressive strength, the minimum strength was 4.7 MPa (50% PS) and the highest was 35.5MPa (90% OPC 10%POFA) in 28 days of curing for novel binder. Other than that, the compressive strength without using POFA recorded minimum strength 8.1MPa (50%PS) and highest strength is 43.1 MPa (100% OPC). By using OPC as a binder, only Indeno (1,2,3- cd) pyrene was successfully encapsulated about 83.6% to 95.6% reduction of concentration in matrices. Whereas, another three compounds Benzo (a) anthracene, Benzo (a) Pyrene, Dibenzo (ah) anthracene were successfully encapsulated more than 75% reduction of concentration when POFA was used to replace cement in matrices. POFA is one of the materials that contain high unburned carbon approved as a novel binder in the S/S method, especially handle with PAHs. In addition, the S/S method with POFA shows the high potential in encapsulated of high rings PAHs.